2017
DOI: 10.1080/23328940.2017.1373896
|View full text |Cite
|
Sign up to set email alerts
|

Thermal imaging reveals sizable shifts in facial temperature surrounding yawning in budgerigars (Melopsittacus undulatus)

Abstract: Accumulating comparative and interdisciplinary research supports a brain cooling function to yawning. In particular, previous research has shown significant decreases in both brain and skull temperature following yawning in mammals. In a recent study using a thermal imaging camera, significant reductions in both the cornea and concha temperature were observed following yawns in the high-yawning subline of Sprague-Dawley rats. Here, we performed a similar experiment to investigate shifts in facial temperature s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…In support of this view, yawns tend to cluster around major transitions of activity (Baenninger, Binkley, & Baenninger, 1996), important daily events (Baenninger 1987), and stressful situations and stimuli (Miller, Gallup, Vogel, & Clark, 2010;Eldakar, Tartar, Garcia, Ramirez, Dauzonne & Gallup, 2017). Moreover, yawns are linked with indicators of neurophysiological arousal (Sato-Suzuki, Kita, Oguri, & Arita, 1998;Sato-Suzuki, Kita, Seki, Oguri, & Arita, 2002;Seki, Nakatani, Kita, Sato-Suzuki, Oguri, & Arita, 2003;Kasuya, Murakami, Oshima, & Dohi, 2005;Kita, Kubota, Yanagita, & Motoki, 2008; but see Guggisberg, Mathis, Herrmann, & Hess, 2007) and followed by significant decreases in brain and skull temperature (Shoup-Knox, Gallup, Gallup, & McNay, 2010;Equibar, Uribe, Cortes, Bautista, & Gallup, 2017;Gallup, Herron, Militello, Swartwood, Cortes, & Eguibar, 2017). Ultimately, these neurovascular changes may improve aspects of cognitive processing (Miller et al, 2010;Miller, Gallup, Vogel, & Clark, 2012).…”
Section: Introductionmentioning
confidence: 97%
“…In support of this view, yawns tend to cluster around major transitions of activity (Baenninger, Binkley, & Baenninger, 1996), important daily events (Baenninger 1987), and stressful situations and stimuli (Miller, Gallup, Vogel, & Clark, 2010;Eldakar, Tartar, Garcia, Ramirez, Dauzonne & Gallup, 2017). Moreover, yawns are linked with indicators of neurophysiological arousal (Sato-Suzuki, Kita, Oguri, & Arita, 1998;Sato-Suzuki, Kita, Seki, Oguri, & Arita, 2002;Seki, Nakatani, Kita, Sato-Suzuki, Oguri, & Arita, 2003;Kasuya, Murakami, Oshima, & Dohi, 2005;Kita, Kubota, Yanagita, & Motoki, 2008; but see Guggisberg, Mathis, Herrmann, & Hess, 2007) and followed by significant decreases in brain and skull temperature (Shoup-Knox, Gallup, Gallup, & McNay, 2010;Equibar, Uribe, Cortes, Bautista, & Gallup, 2017;Gallup, Herron, Militello, Swartwood, Cortes, & Eguibar, 2017). Ultimately, these neurovascular changes may improve aspects of cognitive processing (Miller et al, 2010;Miller, Gallup, Vogel, & Clark, 2012).…”
Section: Introductionmentioning
confidence: 97%
“…Yawning is characterized by a powerful gaping of the jaw with deep inspiration, followed by a temporary period of peak muscle contraction and a passive closure of the jaw during expiration 1 . Physiologically, yawns enhance intracranial circulation 2 and facilitate brain cooling 3–5 , which in turn could serve to promote cortical arousal 6 and state change 7 during behavioral transitions. Contagious yawning, which represents the reflexive triggering or release of this response as a result of sensing yawns in others, is a well-documented phenomenon in humans, as seeing, hearing and even thinking about yawning can induce yawn contagion 7,8 .…”
Section: Introductionmentioning
confidence: 99%
“…In fact, 10 s after a yawn happens, there is a reduction in both facial areas that correlates with the reduction in the cortical temperature measured with implanted thermocouple probes in non-HY rats that then returns to basal levels within a short time period (Shoup-Knox et al, 2010;Eguibar et al, 2017b). In another study, we demonstrated in budgerigars that the beak temperature decreased when a yawn happened (Gallup et al, 2017). These experimental data indirectly support the thermoregulatory role of yawning, but it is necessary to obtain more empirical data to support the hypothesis.…”
Section: Introductionmentioning
confidence: 62%